Antimicrobial activities of crude solvent extract and synthesized silver nanoparticles of Opuntia ficus-indica L. Cladodes (Bangladesh Journal of Botany, 2020)
Opuntia ficus-indica cladodes was examined for their antimicrobial activities by using crude extract and synthesized silver nanoparticles against human pathogenic microbial strains, namely Staphylococcus aureus, Klebsiella pneumoniae, Klebsiella oxytoca, Proteus mirabilis and Candida albicans. All extracts demonstrated moderate activity against the tested microbes in a range between 0.53 and 2.33 cm. The maximum inhibition activity was found to be against K. pneumoniae while the lowest against S. aureus. Synthesized silver nanoparticles (Ag-NPs) showed inhibition activities between 1.82 and 2.03 cm. The maximum activity was recorded against K. oxytoca, while the lowest activities against P. mirabilis. In context of antimicrobial activity, there was no significant difference either solvent crude extract or synthesized silver nanoparticles against tested microbes. Therefore, crude extracts of O. ficus-indica cladodes or Ag-NPs could be used as an alternative natural drug.